Implant surface design for improved implant stability - a study on Ti6Al4V dense and cellular structures produced by selective laser melting - Bartolomeu, Flávio (2019)
Focusing on implant surface design, aiming to improve implant primary stability, SLM technology was explored to produce dense and cellular structured Ti6Al4V specimens. The SLM specimens and also a commercial casted/forged Ti6Al4V group, were sandblasted and acid-etched to obtain a moderate surface roughness topography, typically used in implant manufacturing. Ti6Al4V-bone interaction and tribological performance were assessed by performing sliding tests aiming to replicate in some extension the insertion of a hip implant. The results shown a 24 and 32% higher kinetic friction coefficient values when comparing the cellular structures with the conventional casted/forged Ti6Al4V. These friction results together with a high amount of adhered bone are promising evidences of a higher efficiency of Ti6Al4V cellular structures for enhancing implant stability.